Analysis Bibliometric: Character Education Research in Elementary Schools on One Decades - Yolandini, Bella; Suabuana, Cik; Muhammad, Ilham; Triansyah, Fadli Agus (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Character education is an educational process that seeks to shape a person's personality or character in order to instill them with moral ideals, ethics, and positive attitudes. Character education focuses not just on academics, but also on the development of personality traits such as attitudes, values, morality, empathy, cooperation, and creativity. Objective study This that is to find out trends and identify publications related to character education in elementary schools, and visualize them. The research method used is a bibliometric method or analysis related to character education in elementary schools. The analysis used is evaluative and descriptive bibliographic analysis. The subjects in this study were 164 publications collected from the database dimensions according to the specified keywords . The results of the study show that the number of publications related to character education in elementary schools in Indonesia has increased in recent years, starting from 2017 to 2021. The highest number of documents is at the institution or university "Indonesia University of Education” with 6 documents, in the journal “Journal of Physics Conference Series” with 5 documents, then in an article (Suriansyah, 2015) with the title “Leadership Strategies of Principals, Teachers, Parents, and Communities in Shaping Student Character”. character Building is the most widely used character education keyword together with 133 events, keywords with new themes such as “character education” is not directly related to the keyword “govermnet”. This means that new themes and keywords that are not directly related can be useful for further research that wants to research related to this field.